2018
DOI: 10.3390/md16090309
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Enhancement and Anti-Inflammatory Activities of Fatty Acids Extracted from Halocynthia aurantium Tunic in RAW264.7 Cells

Abstract: Halocynthia aurantium, an edible ascidian species, has not been studied scientifically, even though tunicates and ascidians are well-known to contain several unique and biologically active materials. The current study investigated the fatty acid profiles of the H. aurantium tunic and its immune-regulatory effects on RAW264.7 macrophage cells. Results of the fatty acid profile analysis showed a difference in ratios, depending on the fatty acids being analysed, including those of saturated fatty acids (SFA), mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 42 publications
(45 reference statements)
3
29
0
Order By: Relevance
“…The higher levels of n -3 FAs present in the −Org resulted in a higher n -3/ n -6 ratio, with FAs 18:4 n -3, EPA, and DHA being the main contributors to this trend. This finding is consistent with Monmai et al [ 35 ], as these authors verified that in the edible ascidian Halocynthia aurantium n -3 FAs were present in much higher levels than n -6 FAs. Likewise, Zhao and Li [ 37 ] documented that tunics and inner body tissues of ascidians Halocynthia roretzi , Styela plicata , Ascidia sp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher levels of n -3 FAs present in the −Org resulted in a higher n -3/ n -6 ratio, with FAs 18:4 n -3, EPA, and DHA being the main contributors to this trend. This finding is consistent with Monmai et al [ 35 ], as these authors verified that in the edible ascidian Halocynthia aurantium n -3 FAs were present in much higher levels than n -6 FAs. Likewise, Zhao and Li [ 37 ] documented that tunics and inner body tissues of ascidians Halocynthia roretzi , Styela plicata , Ascidia sp.…”
Section: Discussionsupporting
confidence: 92%
“…Knowledge on ascidians’ FA profiling is still poorly explored. However, some studies have already confirmed that ascidians present a high n -3/ n -6 ratio [ 3 , 35 ] and high values of EPA and DHA [ 36 ], establishing ascidians as a potential new bioresource for n -3 fatty acids-rich marine lipids [ 3 , 37 , 38 ]. Hassanzadeh [ 38 ] concluded that the FA profile of ascidians presented similar values to that of fish oil and, therefore, considered ascidians as a good alternative for fish oil in the formulation of aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…TNF- α is also involved in lipid metabolism. It stimulates the release of free fatty acid (FFA), which in turn promotes the release of TNF- α from macrophages, eventually enhancing lipid accumulation in the liver [ 52 , 53 ]. By directly targeting the intracellular insulin signal transduction system, TNF- α can enhance insulin resistance through upregulating suppressor of cytokine signaling 3 (SOCS-3) [ 54 ] and inhibiting adiponectin activity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total volume of real-time RT-PCR reaction mixture was 20 μL with a 96-well format, included 5.5 μL cDNA template, 2 μL primer mixture (10 μM, 1 μL forward and reverse primer each), 2.5 μL DEPC-treated water, 10 μL TB Green ® Premix Ex Taq™ II (Takara Bio Inc., Kusatsu, Shiga, Japan). All primers were obtained from Macrogen (Seoul, Korea), and sequences were referenced from Chaiwat Monmai et al [ 36 ]. The primer sequences used are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%